An empirical model for predicting wave attenuation inside vegetation domain. (1st August 2022) - Tang, Xiaochun; Liu, Philip L.-F.; Lin, Pengzhi; Jiang, Yun; Lin, Yu-Hsi
Abstract: An empirical model for wave attenuation predictions when periodic waves propagate through vegetation domain is presented based on the dimensional analysis. A new nondimensional parameter K a L which represents the averaged wave attenuation per wavelength in the whole vegetation domain is introduced to denote the wave energy dissipation due to the presence of vegetation stems. The wave attenuation can be predicted by the multiplications of several nondimensional terms containing both wave and vegetation parameters without C D value. The model was firstly calibrated with emergent vegetation cases, and the applicability of Dalrymple et al. (1984)'s model was studied with the same datasets. The comparisons showed the empirical model performed better than Dalrymple et al. (1984)'s one, especially for cases with non-cylindrical stems, incident irregular waves and relatively dense vegetation domain. Then, the empirical model was validated with submerged cases in the literature and also floating cases conducted in the present study. After that, the influence of vegetation domain vertical positions on wave attenuation is discussed based on the validated model, and the non-dimensional vegetation diameter term in the model is changed and analyzed. Moreover, the simplification of the model which substitutes the U r s e l l number for wave nonlinearity and relative water depth is implemented. Highlights: An empirical model was presented to predict the wave attenuation without C D value. A series of laboratory experiments of periodic waves with floating vegetation domain were conducted and the variations of wave heights were measured. The predicted wave attenuation compared well with the measured data for both emergent, submerged and floating vegetated cases, and the comparisons were better than that of Dalrymple et al. (1984)'s model. The floating vegetation would dissipate more wave energy than the submerged vegetation with same vegetation parameters, especially for cases with relatively larger k h .